The Effect of Perceived CEO Overconfidence on Consumers' Product and Brand Evaluations - Lara Katharina Hilgert (Junior Management Science (JUMS), 2020)
This research examines the impact of CEO overconfidence as a mediator of consumer attitudes towards products and brands as well as its influence on perceived brand personality. The results of the study show that revealed verbally communicated overconfidence leads to lower ratings of the product, a lower general attitude towards the brand, lower trust in the brand and lower ratings of descriptiveness regarding the brand personality trait competence. The negative impact of CEO overconfidence is most influential on the participants' trust in the brand. The study additionally observed participants' evaluations of perceived CEO overconfidence and their brand attitudes regarding well-known brands. The results show that participants' general attitude towards a brand and trust in a brand were lower when they perceived the CEO as more overconfident. The insights gained through this study have important implications for the literature on the impact of overconfidence on an individual's status and the literature on CEO endorsement. Additionally, this research can act as a guidance for CEOs and executives on how his or her trait of overconfidence affects consumers' and how the company's performance may be affected by this relationship.
Keywords: 650; Overconfidence; leadership; consumer; perception; brand